Haptoglobin and C-Reactive Protein—Non-specific Markers for Nursery Conditions in Swine - Hennig-Pauka, Isabel; Menzel, Anne; Boehme, Till Robert; Schierbaum, Horst; Ganter, Martin; Schulz, Jochen (Frontiers in Veterinary Science, 2019)
A quality concept for production in the pork market includes granting a good health status of pigs from birth to slaughter. This concept is a precondition for animal welfare as well as reducing antibiotic usage in farm animals. The demand for fighting bacterial antimicrobial resistance in humans, animals and in the environment is one driving force for the development of innovative technical solutions to improve husbandry. Maintenance of a good health status in pigs depends on early detection of a disturbance in homeostasis in critical phases of life. This can be measured by non-specific biomarkers as acute phase proteins. In this project, husbandry conditions and health status in nursery pigs were monitored in an autumn and winter nursery period from weaning to the end of nursery in two compartments with 180 pigs each. It was investigated whether a slight modification in indoor climate achieved by a new ammonia sensory technology coupled with the electronic control unit of the forced ventilation system ensuring ammonia levels lower than 5+3 ppm in one compartment led to a better health status in piglets in comparison to the control compartment. In the examined nursery periods in different seasons, ammonia concentrations in the experimental compartment were significantly lower than in the control compartment, thus proving the functionality and efficacy of the technical system. Production parameters as feed conversion rate and average daily weight gain were slightly improved in the experimental compartment without implementing other measures. Multifactorial analysis of variance resulted in a significant influence of season, daily quarter and compartment on ammonia concentration. The challenge to preserve a high health status of piglets also during suboptimal outside climate in the transitional season was reflected by an increase in the acute-phase proteins haptoglobin (Hp) and C-reactive protein (CRP) in autumn compared to winter. The seasonal influence on concentrations of CRP and Hp superimposed potential influences of the climate modification. New technological concepts to reduce noxious gases and dust in the animal environment as well as emissions, which in parallel guarantee optimal temperatures also during extreme weather conditions, can be evaluated by clinical data in combination with biomarkers.